Stimulated Emission of Active Media in the Red Spectral Range; Russian Physics Journal; Vol. 59, iss. 1 - Kopylova T. N. Tatjyana Nikolaevna; Gadirov R. M. Ruslan Mukhamedzhanovich; Nikonov S. Yu. Sergey Yurjevich; Valiev R. R. Rashid Rinatovich; Telminov E. N. Evgeny Nikolaevich; Nikonova M. B. Mark Borisovich; Kopylova E. N. Elena Nikolaevna; Solodova T. A. Tatjyana Aleksandrovna; Alekseeva V. I. Vera Ivanovna; Marinina L. E. Lyubov Egorovna; Savvina L. P. Lyubov Prokofjevna (Optics and spectroscopy, 2016)
Title screen